GNSS DATA MONITORING DROUGHT: CURRENT APPLICATIONS AND OUTLOOK - Cui, J. Y.; Wan Aris, W. A.; Musa, T. A. (Journal of Engineering and Technology (JET), 2025)
Continuous and dense observations from the Global Navigation Satellite System (GNSS) have emerged as a pivotal tool for drought monitoring. Currently, the most prevalent approaches for drought monitoring using GNSS data fall into two categories: hydrological drought monitoring, which relies on the inversion of terrestrial water storage (TWS) variations, and meteorological drought monitoring, derived from atmospheric precipitable water vapour (PWV). While GNSS has become a focal point of research in hydrogeology, comprehensive studies systematically exploring the use of GNSS data in extreme drought monitoring still need to be expanded. Few studies have provided a comprehensive and systematic overview of meteorological and hydrological drought monitoring based on GNSS data. This study utilizes bibliometrics to analyze GNSS-based extreme drought monitoring research, explores its principles and methods, and discusses current limitations and future directions, aiming to guide future research on regional drought changes and applications using GNSS technology.